National Plan for Books and Reading of Peru 2006-2021 - (Promolibro), Consejo Nacional de Democratización del Libro (2005)
The National Book and Reading Plan of Peru (PNLL) is a document that seeks to respond to the reality of our country, characterized by the expansion of functional illiteracy, large bilingual sectors, predominance in many areas of mother tongues, as well as oral tradition, little reading practice and less writing. Likewise, there is a lack of spaces that bring the Peruvian population closer to written culture, such as libraries, well-equipped schools, up-to-date universities, written press.